Partial sequence of 16S ribosomal RNA gene for Lactococcus lactis strain A5 - Tengku Abdul Hamid, Tengku Haziyamin; Zin, N.H.M. .; Nur Shazana, Azhar (2015)
This is a record for Partial sequence of 16S ribosomal RNA gene for Lactococcus lactis strain A5 isolated from the intestines of Claria macrocephalus, Malaysian broadhead catfish. This sequence is assigned with a NCBI accession number of KP064393.